Design and construction of a 9 MeV γ-ray source based on capture of moderated plutonium–beryllium neutrons in nickel. (January 2023) - Söderström, P.-A.; Balabanski, D.L.; Ban, R.S.; Ciocan, Gh.; Cuciuc, M.; Dhal, A.; Fugaru, V.; Iancu, V.; Rotaru, A.; Şerban, A.B.; State, A.; Testov, D.; et al.
Abstract: We have designed and constructed a high-energy γ -ray source for detector characterisation and calibration. The source is a composite type based on a plutonium–beryllium neutron emitter embedded in a paraffin moderator, which is homogeneously mixed with nickel powder. The 9 MeV γ -ray source produces approximately 450 photons per second in 4 π when 2 . 2 × 1 0 5 neutrons per second are emitted, corresponding to a surface flux of 9 MeV γ -rays of approximately 2 . 5 × 1 0 − 6  cm −2 per emitted neutron. Here we discuss the properties and design of this source, including the characterisation of homogeneity and high-energy γ -ray emission spectra. Highlights: A source of 9 MeV gamma rays based on neutron capture in nickel has been constructed The source has been characterised with a radioisotopic PuBe primary neutron field The gamma-ray spectrum has been evaluated in the ELIGANT-GN and the ELIADE arrays